Immobilization of lipase candida rugosa on nylon 6 polymer grafted with poly venylbenzyl chloride (PVBC) - Abd Halin, Nur Iilani; Al-Khatib, Ma'an Fahmi Rashid; Mohd. Salleh, Hamzah (2017)
Enzyme is well known as an excellent catalyst for many biological systems. In spite of that, enzyme properties such as high activity, selectivity and specificity should be enhanced to improve products yields and reusability. Hence, immobilization of enzymes on carrier supports is gaining attention as alternative for free enzymes. In this study, lipase Candida rugosa was immobilized on nylon 6 polymer grafted with poly vinylbenzyl Chloride (PVBC). Nylon 6 polymer was selected for its strength, low cost and high loading capacity of enzyme meanwhile grafted with PVBC will improve the performance by selecting a functional group for enzyme binding.